Exploring user-generated content for improving destination knowledge - António, Nuno (2020)
Antonio, N., Correia, M. B., & Ribeiro, F. P. (2020). Exploring user-generated content for improving destination knowledge: The case of two world heritage cities. Sustainability (Switzerland), 12(22), 1-19. [9654]. https://doi.org/10.3390/su12229654